Chronotype and depression in adolescence: Results from a UK birth cohort study - Dimitris I. Tsomokos; Elizabeth Halstead; Eirini Flouri (JCPP Advances)
Abstract Background Research has established a bidirectional association between sleep disturbances and depression in both adults and youth, as well as links between depression and circadian rhythms and chronotype, predominantly in adult populations. However, the link between chronotype and depression in the general adolescent population, independently of poor sleep and prior mental health problems, remains unclear. Methods This study investigated the association between time‐to‐sleep (TTS) and depressive symptoms in middle adolescence (age 14 years) using data from a large, nationally representative birth cohort from the UK. The relationship between TTS and self‐reported number of depressive symptoms was adjusted for individual, family, and neighborhood characteristics, including sleep quality, earlier mental health, diet and family meal routines, body‐mass index, screen time, physical activity, chronic illness, special educational needs, peer victimization, socioeconomic status, maternal mental health, area safety and the built environment (air pollution). Results An “evening” chronotype was positively associated with depressive symptoms, and biological sex moderated this association—with eveningness being more strongly related to depressive symptoms in females. TTS inconsistency between non‐school and school nights was associated with depressive symptoms and sleeping later on non‐school nights predicted fewer depressive symptoms. The results were robust to further sensitivity analyses that used the sleep midpoint on non‐school nights and controlled for sleep duration. Limitations This was a correlational study. The independent and dependent variables were self‐reported, and there was no clinical screening for sleep disorders. The TTS variables were provided in crude hour slots. Conclusions A robust association was found between evening chronotype and depressive symptoms in middle adolescence, even after adjustment for a wide range of confounders. Eveningess and depressive symptoms were more strongly associated in females.